Seasonal switching between habitats and changes in abundance of Goosanders Mergus merganser within a Scottish river system - Marquiss, M; Duncan, K (Wildfowl, 2025)
Systematic weekly counts during 1988, in five wetland habitats within the Dee watershed, showed that Goosanders were most abundant on the upper river in spring and summer, on the lower river in late summer, autumn and winter, and on lochs in late winter and spring. Many birds were in pairs in winter and spring, but adult males were absent from June to October, when the population was successively dominated by females, then females with broods, then juveniles. Most females nested far up tributaries and moved downstream with small ducklings to nursery areas on the main stem. Once grown, juveniles possibly moved downstream again before they dispersed from the watershed. Counts on a sample of river sections in mid-April quantified a strong inverse relationship between Goosander density and elevation, and the total population then was estimated to be 173 (including about 61 pairs). A census of the whole river in July estimated a population of 278 birds (including 32 broods) and in December, 66 birds. It is argued that the use of various habitats was associated with food availability, security from predators, pairing and nesting.